2013
DOI: 10.1111/j.1600-048x.2013.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Tawny owl vocal activity is constrained by predation risk

Abstract: Th e vocal behaviour of birds may be infl uenced by many factors, including the risk of being detected by a predator. In Do ñ ana Protected Area, the tawny owl co-exists alongside its intraguild predator, the eagle owl Bubo bubo . We considered four scenarios to study the vocal behaviour of tawny owls at dusk by analysing: A) the calling rate of all males in 29 sites; B) the calling rate at dusk of males living within the home range of the intraguild predator; C) the calling rate of males living within the hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…This study joins several others investigating the effects of predation danger on the singing behavior of songbirds (Akçay et al 2016;Schmidt and Belinsky 2013;Robertson et al 2010;Duncan and Bednekoff 2006;Fontaine and Martin 2006a;2006b ). The effect is not restricted to passerines; tawny owls (Strix aluco (Linnaeus, 1758)) exposed to the calls of a larger intraguild predator reduced their calling rate (Lourenço et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This study joins several others investigating the effects of predation danger on the singing behavior of songbirds (Akçay et al 2016;Schmidt and Belinsky 2013;Robertson et al 2010;Duncan and Bednekoff 2006;Fontaine and Martin 2006a;2006b ). The effect is not restricted to passerines; tawny owls (Strix aluco (Linnaeus, 1758)) exposed to the calls of a larger intraguild predator reduced their calling rate (Lourenço et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Also, individuals calling more frequently, such as males or fledglings, or when they exhibit more exposed behaviours (e.g. during displays) may be more easily detected by superpredators (Hakkarainen and Korpimäki 1996, Lourenço et al 2013, Hoy et al 2015. These three components also represent what is commonly referred as prey availability, which in superpredation concerns only mesopredator species.…”
Section: Encounter Probabilitymentioning
confidence: 99%
“…Previous studies have inferred that detection probabilities of spotted owls ( Strix occidentalis ) were lower at sites where the more aggressive barred owls ( Strix varia ) are undergoing expansion into spotted owl habitat (Olson et al , Crozier et al , Bailey et al ). Furthermore, Lourenço et al () suggested that the detectability of tawny owls ( Strix aluco ) decreased at sites where eagle owls ( Bubo bubo ), their predators, were present. In contrast, the few studies that have reported higher calling rates in response to the calls of another owl species have been associated with mobbing behavior or inter‐specific territoriality (Ganey , Boal and Bibles , Crozier et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfavorable detection conditions such as wind speed, environmental noise, and cloud cover can influence the ability of researchers to detect owls (Fisher et al , Andersen ) and lunar cycles appear to influence communication and activity patterns of owls and their prey (Clarke , Penteriani et al ). Furthermore, the calling rates of owls may be affected by the risk of being detected by an intraguild predator (Lourenço et al ), or by the presence of a dominant owl in the area (Olson et al ). Thus the number of sampling units occupied by an owl species of interest and their detection probabilities can be underestimated if environmental or social factors are not considered.…”
mentioning
confidence: 99%